Phenyliodonium Diacetate Mediated Carbotrifluoromethylation of Quinoxalin‐2(1H)‐ones. Issue 6 (14th April 2019) - Xue, Wenxuan; Su, Yingpeng; Wang, Ke‐Hu; Cao, Lindan; Feng, Yawei; Zhang, Weigang; Huang, Danfeng; Hu, Yulai
Abstract: An efficient method for the synthesis of 3‐trifluoromethylquinoxalin‐2(1 H )‐ones by a direct trifluoromethylation of quinoxalin‐2(1 H )‐one derivatives has been developed under transition‐metal‐free conditions. The strategy uses cheap and commercially available PhI(OAc)2 as a promoter, TMSCF3 as a trifluoromethylation reagent in the presence of catalytic amount of benzoquinone to give the products in good yields. Abstract : Metal‐free Synthesis : 3‐Trifluoromethylquinoxalin‐2(1 H )‐ones are synthesized via direct carbotrifluoromethylation of quinoxalin‐2(1 H )‐one derivatives in the presence of phenyliodonium diacetate.